Biological and decorative properties of juniper virginiana, used in landscaping roads and streets of Tashkent - Ubaydullayev Farkhod Bakhtiyarullaevich; Ergashev Khahramon Khushvaktovich (Zien Journals, 2024)
Juniperus virginiana has a pyramidal branch, which in its natural state forms a branched and sparse branch. For landscaping purposes, it is necessary to artificially shape tree branches. In terms of the density of its branches, juniper virginiana belongs to the group of compact trees.
Keywords: virginiana; pyramidal; terms; branched